Teacher Online Qualification Framework - Alfredo Soeiro (2020)
Implementation of digital technologies into education process is nothing new, distance and online education has been present for the decades. But with the COVID-19 pandemic educational institutions, teachers and educators had to move suddenly to fully online teaching and learning. And many of them has not been prepared for that, especially lacking skills in digital pedagogy. How to implement digital technologies skilfully, equitably and effectively to support high quality and inclusive education is one of the most important issue now.